Risk Assessment for Birds and Mammals - European Food Safety Authority (EFSA Journal)
Abstract The revised Guidance Document on Risk Assessment for Birds and Mammals on the basis of the Scientific Opinion of the PPR Panel on the Science behind the Guidance Document on Risk Assessment for Birds and Mammals (The EFSA Journal (2008) 734: 1–181) and its Appendices has been finalised based on the decisions of the Joint WG consisting of representatives from the European Commission, nominated Member States and technical experts from EFSA.